Comparison of Three Browser Performances - Stefanus Lintang Timur Aji Pamungkas (SISFORMA, 2014)
In this era of globalization and modernity, it is important to obtain information, and the role of Internet in providing information is indispensable. The existence of the World Wide Web technology makes it easy for people to surf various websites. The elements on the website are the code javascript, css, and HTML5